The validity of teacher nomination of pupils for inclusion in a gifted programme in ''Indian'' schools - Chhagan, Ramesh C (My University, 2014)
The aim of this study was to investigate the validity of teacher nomination of pupils for inclusion in a giftei programme in "Indian" schools. Correlations between teacher nominations and the Renzulli Satin* Scale (FRS) were used to test the validity of teacher nomination and highly significant correlations were found . The RRS was adopted because it covered * broader, interactive, multiple criteria definition than the more traditional, narrow, measures of intelligence< As the RRS hi reliability and validity only in respect of an American context a pilot study was undertaken to validate the RRS as a test of intelligence for South African children. The pilot study correlated the intellectual category of RRS scores with scores on the Junior South African Individual Scale (JSAIS) the latter being a unidimensional measure of intelligence. Correlations obtained were highly significant suggesting that the RRS was valid as a measure o' intelligence. At the same time it had the added advantage of considering other dimensions of giftedness (namely, task commitment and creativity). The results of the correlations between the RRS and teacher nomination suggest that teacher nomination is a valid, cost effective and reliable method of of giftedness standardised id established
A RESEARCH PROJECT SUBMITTED TO THE FACULTY OF EDUCATION - DIVISION OF SPECIALISED EDUCATION - UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG - TOWARDS THE DL'GREE OF MASTER OF EDUCATION (EDUCATIONAL PSYCHOLOGY). JOHANNESBURG, 1990.